PENYULUHAN KESADARAN HUKUM SEJAK USIA DINI DI PANTI ASUHAN ISTANA YATIM AL-JUFRI - Christiani Prasetiasari; Nicha Suwalla; Agus Siagian; Auliya Fitri Zaiana; Juli Artha Lubis (LPPM Universitas Bina Bangsa, 2024)
The existence of law in society functions to maintain order, peace and harmony, as well as aligning human interests or needs in society and the state. The role of the law applies to every individual, including students, therefore it is necessary to provide legal awareness education from an early age, especially for the object of this service at the Al-Jufri Orphanage Palace. Understanding the law is not only about avoiding violations, but also about instilling good values, such as justice, freedom and responsibility. Legal education needs to be taught from an early age. This aims to provide opportunities for students to understand how the law affects their daily lives, from basic rights, such as the right to quality education, to responsibilities as citizens